Investigating the Impact of Antibiotic Exposure Duration on Bacterial Resistance in Chicken Farm Drinking Water - Ornela Nzinou Batchanou; Claude Bérenger Ngantchouko Ngalemo; Pascal Dieudonné Chuisseu Djamen; O’Neal Dorsel Youté; Baladur Ekono; Therese Abong; Adolarice Nana Feukeu; Pierre René Fotsing Kwetche (Archives of Current Research International, 2025)
Antibiotic-resistant bacteria have increased as a result of antibiotics and other selective agents misuse and overuse. The present pilot investigation aimed at determining the length of time that drinking water specimens containing antibiotics should be kept on chicken farm with minimal risk of selecting resistant bacterial strains. All administrative requirements were fulfilled prior to the first steps through the process which began with a questionnaire, then isolation of Escherichia coli, Morganella morganii, Proteus mirabilis from animal drinking water (> 72 h), and initial susceptibility tests. These isolates first underwent subculture over 15 days in antibiotic-free environments to appreciate susceptibility patterns based on the inhibition diameters. Secondly, the subcultures obtained from the 15th subcultures were exposed to antibiotic suspensions made according to the manufacturer’s instructions regarding their use on farms. Several findings were expected from this second step: a– the time between the suspension preparation and development of the first population on agar plates and b– the susceptibility tests on the first populations and on the one observed at the 24th h. These tests were repeated 15 times. All identifications and susceptibility testing were conducted according to standard guidelines. Doxycycline (42%), Colistin (39%), and Oxytetracycline (13%) were identified as the most commonly used antibacterial agents. Overall, 64% of the population renewed the water after 24 or 48 hours; while 36% kept it for of 12-24 hours on average. Gradual increased susceptibility was invariably observed in bacteria populations grown serially in antibiotic-free environments. Exposed to antibiotics, it was observed that average time for minimal risk of resistance selection was species-dependent and antibiotic-dependent; and that susceptibility gradually decreased as exposure time extended. Overall, the time recommended to keep antibiotic solutions on farms depends on bacterial types and the antibiotic used, imposing the necessity to know, at least the major bacterial types targeted before any intervention regarding antibiotics in animal drinking water is undertaken. This management pattern will thereby, associate biosafety and biosecurity in addressing the selection of resistance traits in bacteria.